AI-Integrated ICT Tools for Teaching Ancient Indian Social Structures: A Modern Pedagogical Framework for Caste, Creed, Race, Other Social Structures, and their Studies (International Journal of Food and Nutritional Sciences, 2023)
Ancient Indian social structures particularly caste, creed, race, and hierarchical formations remain central to understanding the subcontinent’s historical and socio-cultural evolution. Traditional teaching approaches often struggle to convey this complexity, especially in increasingly digital learning environments. Recent advances in Artificial Intelligence (AI) and Information and Communication Technology (ICT) offer new possibilities for creating immersive, ethical, and context-rich pedagogy in humanities and social-science education.